Globalisation contested : An international political economy of work - Amoore, Louise (Manchester University Press, 2002)
This exciting book provides an illuminating account of contemporary globalization that is grounded in actual transformations in the areas of production and the workplace. It reveals the social and political contests that give 'global' its meaning, by examining the contested nature of globalization as it is expressed in the restructuring of work. Rejecting conventional explanations of globalization as a process that automatically leads to transformations in working lives, or as a project that is strategically designed to bring about lean and flexible forms of production, this book advances an understanding of the social practices that constitute global change. Through case studies that span from the labour flexibility debates in Britain and Germany, to the strategies and tactics of corporations and workers, the author examines how globalization is interpreted and experienced in everyday life. Contestation, she argues, is about more than just direct protests and resistances. It has become a central feature of the practices that enable or confound global restructuring. This book offers students and scholars of international political economy, sociology and industrial relations an innovative framework for the analysis of globalisation and the restructuring of work.
English
Keywords: Globalization; economics; globalization; politics; europe; Germany; Industrial relations; Labour economics; Multinational corporation; Neoliberalism; Social change